Education Strategy As Business: Talktune Short Course In Learning German For Beginners - Firdaus, Heliconia Putri; Fedora, Claresta Faustina; Mayangsari, Indah; Prameswari, Pradypta Nurziyah (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2024)
MOOC (Massive Online Open Course) is a flexible and accessible form of online learning, allowing learners to choose their own learning time. Online short courses, such as TalkTune, offer comprehensive German language teaching, with video lessons presented in a short and fun way. The platform caters to various levels of German proficiency, from beginners to B1 level classes. The basic level of competence in German is at Niveau A1-A2, while advanced competence is at Niveau B1-B2. TalkTune also offers an opportunity for individuals to earn additional income by becoming a material provider. With an estimated 900% growth in online courses since 2000, TalkTune can capitalize on this trend and provide instructors with a platform to share their knowledge and skills, potentially increasing their visibility and earning potential. With its efficient scalability, TalkTune can support a large number of users and courses, allowing it to expand quickly and adapt to changing market dynamics.